Association of long‐term exposure to air pollution and dementia risk: the role of homocysteine, methionine. (20th December 2022) - Rizzuto, Debora; Hooshmand, Babak; Vetrano, Davide Liborio; Wu, Jing; Grande, Giulia
Abstract: Background: Growing evidence associates long‐term exposure to air pollution with dementia. The biological mechanisms behind this association are yet unclear. We aimed to investigate the role played by homocysteine and methionine in the association between air pollution and dementia. Method: Data from 2512 dementia‐free individuals were derived from the ongoing Swedish National study on Aging and Care in Kungsholmen (SNAC‐K). Two major air pollutants (particulate matter ≤2.5µm, PM2.5 and nitrogen oxides, NOX ) were assessed yearly from 1990, using dispersion models for outdoor levels at residential addresses. The hazard of dementia was estimated using Cox models. The potential mediating or modifying effects of homocysteine and methionine were analysed through the counterfactual approach. Result: Over a mean follow‐up time of 5.18 years (SD: 2.96), 376 incident dementia cases were identified. We observed an up to 70% increased hazard of dementia per unit increase in PM2.5 levels during the previous five years (HR: 1.71; 95%CI: 1.33‐2.09). We found that approximately 50% (95%CI: 8.9‐97.7) of the total effect of PM2.5 on dementia was due to mediation (7.5%; 95%CI:1.8%‐13.3%) and/or interaction (50%; 95%CI: 5.0%‐ 94.9%) with homocysteine. Higher levels of methionine reduced the dementia risk linked to PM2.5 exposure by 31% (HR: 0.69; 95% CI: 0.56 – 0.85). No statistically significant mediation effect was found through methionine in the association between PM2.5 and dementia. Similar but attenuated results have been obtained for NOx. Conclusion: High levels of homocysteine enhanced the dementia risk associated with air pollution exposure, whereas high methionine reduced such a risk.